The spectacular revenge of Suzi Sims - French, Vivian (Edinburgh : Barrington Stoke, 2019)
Sports Day is coming up soon and Suzi's in a great mood - until her class get saddled with mean old Miss Grit as their supply teacher. Miss Grit has it in for Suzi from day one, and worst of all, Suzi's rival Barbie Meek is Miss Grit's class favourite! The terrible duo are about to turn Suzi's life into a nightmare ... will she even make it to Sports Day for her chance to win the race? Hilarious school-based drama from a top-notch pairing
Keywords: Children's stories